Reliability and usefulness of half-squat 1RM estimation through movement velocity in U18 soccer players - Moreno-Navarro, Pedro (European Journal of Human Movement, 2020)
Assessment of strength in youth athletes using as afety , time-efficient and reliable test is crucial for strength and conditioning professionals . The purpose of this study was to examine the reliability of the one-repetition maximum (1RM) estimation through movement velocity in youth soccer players . In addition, the relations hips between 1RM estimation with peak power (PP), jumping and sprinting performance were checked. Material and methods : Twenty-two youth soccer players (16.8±0.6 years ) took part in the study . Participants completed a 1RM estimation in thehalf-squat, squat jump (SJ), counter movement jump (CM J) and 30m s print in three different occasions . Results : The 1RM estimation showed good absolute (SEM <10% ) and relative (I CC>0.7) reliability scores. The estimated 1RM value was significantly lower in the trial 1 compared to the trials 2 and 3. The estimated 1R M and the PP output showed significant correlations (r =0.538-0.560) with jumping and sprinting performance. Discussion: These data suggest the necessity to performat leas to ne familiarizations es s io n to obtain a reliable 1R M estimation through movement velocity in youth soccer players . Once youth soccer players are familiarized with the 1R M estimation protocol, coaches could use this evaluation to obtain a reliable measure of player s ' maximal strength in a time-efficient way La evaluación de la fuerza en los deportistas mediante el uso de un test seguro , eficiente y fiable es crucial para los profesionales del acondicionamiento físico . El objetivo de este estudio fue examinar la fiabilidad de la estimación de la repetición máxim a (1R M ) a través de la velocidad de movimiento en jóvenes jugadores de fútbol. Además , se analizó las relaciones entre la estimación de 1R M con el pico de po tencia (PP), la altura de salto y el sprint. Material y métodos : Veintidós jóvenes jugador es de fútbo l (16,8 ± 0,6 año s ) participaron en el es tudio . Los participantes completaron un tes t de 1R M en media sentadilla, squat jump (SJ), salto en contra movimiento (CM J) y sprint de 30 m en tres ocasiones diferentes . Resultados : La estimación del 1R M mostró buenos valores de fiabilidad absoluta (SEM <10% ) y relativa (I CC> 0.7) . El valor estimado de 1R M fue significativamente menor en la prueba 1 en comparación con las pruebas 2 y 3. La estimación del 1R M y PP mostraron correlaciones significativas (r=0.538-0.560) con el rendimiento en saltos y sprint. Discusión: Estos datos sugieren la necesidad de realizar al menos una sesión de familiarización par a obtener una estimación fiable d el 1R M a través de la velocidad de movimiento en jugadores de fútbol juveniles . Una vez que los jugadores de fútbol juveniles estén familiarizados con el pro toco lo de estimación 1RM , los entrenadores podrían usar esta evaluación para obtener una medida fiable de la fuerza máxima de los jugadores de una mane a eficiente en el tiempo.